2019
DOI: 10.11591/ijece.v9i6.pp4898-4903
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid swarm and GA based approach for software test case selection

Abstract: <span>Being a crucial step and deciding factor for software reliability, software testing has evolved a long way and always attracted researchers due to various inherent challenges. The quality of a software application depends on the effectiveness of the testing carried out during development and maintenance phase. Testing is a crucial but time consuming activity that influences the overall cost of software development. Thus a minimal but efficient test suite selection is the need of the hour. This pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…This research mainly focuses on the quality improvement of component-based software by applying hybrid soft computing-based automation testing techniques. A comparison is made between three parent approaches i.e., GA, ACO, ABC and three hybrid versions i.e., ACO_GA (HACGA) [24], hybrid ABC_Naive Bayes [25], hybrid ABC_GA [26] and their performance is evaluated in terms of execution time, percentage of test cases selected and average branch coverage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This research mainly focuses on the quality improvement of component-based software by applying hybrid soft computing-based automation testing techniques. A comparison is made between three parent approaches i.e., GA, ACO, ABC and three hybrid versions i.e., ACO_GA (HACGA) [24], hybrid ABC_Naive Bayes [25], hybrid ABC_GA [26] and their performance is evaluated in terms of execution time, percentage of test cases selected and average branch coverage.…”
Section: Methodsmentioning
confidence: 99%
“…Various swarm intelligence techniques for regression test case selection over benchmark problems are been compared. Through experimental results they concluded that hybrid PSO outperforms ACO with 0.7 % test case selection [24]. Researchers employed ABC for path coverage by finding optimal fitness value among a range of values [25].…”
Section: Related Workmentioning
confidence: 99%
“…The problem of testing optimization is first converted to graphical search problem and then ACO is applied [9]. Various hybrid approaches with ACO have also been proposed with other techniques such as Genetic Algorithm (GA) which aims to select a minimal test suite for higher fault coverage [10].…”
Section: Related Workmentioning
confidence: 99%
“…W n is the weight of the test path (sum of node weights in test path) and N is the number of nodes in the test path. The score of a test path Score p is calculated by (7), and the test paths are prioritized according to their scores in descending order.…”
Section: Calculating Scores and Prioritizing For Test Pathsmentioning
confidence: 99%
“…Risk-based test case prioritization prioritizes the test cases that concern the major risks that affected the software [1]. Search-based test case prioritization finds the optimal ranking of the test cases by searching from the global space to fit the objectives, such as greedy, genetic algorithm, ant colony [1,2,7]. Some studies used a concept of hybridizing A* algorithm and ant colony optimization to generate and optimize the test paths [8].…”
Section: Introductionmentioning
confidence: 99%